Immersion Calorimetry for the Characterization of PD Catalysts Supported on Activated Carbon - Liliana Giraldo; Juan Carlos Moreno-Piraján (E-Journal of Chemistry)
Activated carbons obtained from coconut peel were oxidized using hydrogen peroxide. Superficial characteristics of these carbons were determined through N2 and CO2 isotherms and functional groups were characterized by TPD. Finally, the microcalorimetry technique was used in order to obtain the immersion enthalpies in diverse liquids and established the relation between them and the results obtained by the other characterization techniques. The results suggested that the immersion calorimetry allow establishing the difference between the supports and the catalysts.